2005
DOI: 10.1111/j.1553-2712.2005.tb01950.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Charlson Comorbidity Index Useful for Predicting Trauma Outcomes?

Abstract: While the CCI can be extrapolated from ICD codes and provides a measure of comorbid condition severity and was associated with mortality, addition of the CCI to prediction models did not result in a substantial improvement in performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 10 publications
6
44
1
5
Order By: Relevance
“…The association of the CCI with mortality after trauma is consistent with prior studies in which higher in-hospital mortality was found in patients with hip fractures with higher CCI scores [9,25].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The association of the CCI with mortality after trauma is consistent with prior studies in which higher in-hospital mortality was found in patients with hip fractures with higher CCI scores [9,25].…”
Section: Discussionsupporting
confidence: 90%
“…With the economic penalties associated with readmission after surgery with the Hospital Readmissions Reduction Program [6,16,19], there now are financial and professional incentives to improve our ability to anticipate complications of treatment. The CCI has been used as a predictor for adverse events [2,9,17,30,[32][33][34]37]. Our study addressed the association of comorbidities as measured by the CCI on readmission and adverse outcomes after orthopaedic surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Despite prolific use, the Charleson Comorbidity Index showed little or limited predictive power on trauma mortality. 18 The incremental risk of death with more comorbid diseases and polytrauma is mainly explained by allostatic load, a dose-dependent physiological stress resulting from chronic 'wear and tear' . 19 Studies that incorporated concomitant injuries on mortality prediction mostly relied on the Injury Severity Score (ISS) with demonstrable effectiveness.…”
Section: Discussionmentioning
confidence: 99%